Design of Web-Based Student Academic Information System - Makkaraka, Andi Muh Reza B; Akbar Iskandar; Wang Yang (Ceddi Journal of Education, 2024)
The management of student academic data often faces challenges due to the reliance on manual processes, which are susceptible to errors and inefficiencies. This study was conducted to design and implement a web-based academic information system aimed at improving the efficiency and accuracy of managing academic data in educational institutions. The development process employed the Rapid Application Development (RAD) methodology, chosen for its iterative and flexible approach, which allows for quick prototyping and feedback integration. Black box testing was used to ensure the system's functionality meets the required specifications and operates effectively under various conditions. User testing results showed that 80% of users rated the system as highly effective, citing its ease of use, real-time data access, and streamlined workflows. The remaining 20% rated the system as effective, highlighting its ability to improve overall academic data monitoring. The system enables students, teachers, and parents to access and monitor academic information efficiently, fostering better communication and decision-making. Furthermore, the findings underscore the system's ability to minimize data errors, enhance the quality of educational services, and contribute to the broader digital transformation of the education sector. This research demonstrates the feasibility and significant impact of implementing web-based solutions in modern educational settings, paving the way for further innovation and adoption of technology in education.